2022
DOI: 10.1155/2022/8367395
|View full text |Cite|
|
Sign up to set email alerts
|

Association between Immunohistochemistry Markers and Tumor Features and Their Diagnostic and Prognostic Values in Intrahepatic Cholangiocarcinoma

Abstract: This study investigated the expression of some frequently used immunohistochemistry (IHC) markers. Besides, we evaluated their correlations with the clinical features and outcomes of intrahepatic cholangiocarcinoma (ICC). Patients who underwent surgical removal of the ICC tumors were followed up for 4 years. The paraffin-embedded sections were used to obtain different markers, including CK7, CK19, CK20, CDX2, Glypican3, Hepa1, Ki-67, Villin, and SATB1. Overall survival in relation to IHC marker expression patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…26 In other studies, the mean age of patients has been reported to range from 37.40 years to 47 years. 13,27,28 A much younger age profile of the patients was reported by an author in 2019 who reported the median age of premalignant and malignant group patients in 25 to 28 years range. 29 In the present study, majority of patients (55%) were in age group 40-49 years.…”
Section: Discussionmentioning
confidence: 89%
“…26 In other studies, the mean age of patients has been reported to range from 37.40 years to 47 years. 13,27,28 A much younger age profile of the patients was reported by an author in 2019 who reported the median age of premalignant and malignant group patients in 25 to 28 years range. 29 In the present study, majority of patients (55%) were in age group 40-49 years.…”
Section: Discussionmentioning
confidence: 89%
“…OR of lymph node metastasis was up to 2.81, indicating the close association between lymph node metastasis and DM, which is not surprising that lymph node could be a way to occur DM [ 18 ]. In previous studies [ 19 , 20 ], age was rarely used as a related variable for DM. However, this study found that the DM risk of patients aged 50 to 64 years was higher than other patients.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study conducted by He et al demonstrated a significant association between the post-surgery survival of iCCA patients and two immunohistochemical markers: while SATB1 indicated poor survival (median survival of 122 days vs. 347 days in SATB1-negative cases, p = 0.04), Villin-positive cases were associated with better OS, with direct correlation with Villin intensity (p = 0.002). This study recommended CK7 assessment in iCCA cases, since it was negatively correlated with lymphatic metastasis in their case series [41]. An interesting study conducted by Yeh et al in Taipei validated C-reactive protein (CRP) as a highly performant diagnostic marker for iCCA, with a 93.3% sensitivity and an 88.2% specificity.…”
Section: Prognostic Perspectivesmentioning
confidence: 93%